Soapberry-Based Liquid Hand Soap with Betel Essential Oil: Formulation, Characterization, and Antibacterial Activity - Ihsan, Muhammad; Tiyana Ramadhini Az Zahra; Hana Pertiwi; Devi Lestariningsih (Journal of Biobased Chemicals, 2026)
Soapberry fruit contains natural saponins with potential as biosurfactant active ingredients in liquid hand soap formulations. This study aimed to formulate and evaluate the physical quality of a liquid hand soap based on soapberry fruit extract, with sodium chloride (NaCl) employed as a viscosity regulator instead of conventional carboxymethyl cellulose (CMC). Formulations were prepared at soapberry extract concentrations of 20% (F1), 25% (F2), and 30% (F3) using Virgin Coconut Oil (VCO) and potassium hydroxide (KOH) via saponification. Physical quality was evaluated through organoleptic assessment and pH measurement in accordance with SNI 2588:2017, supplemented by foam stability and specific gravity as additional physicochemical parameters. All formulations satisfied the SNI 2588:2017 pH requirement (4–10), yielding pH 8 across all extract-containing formulations, while specific gravity ranged from 1.031 to 1.038 g/mL. Foam stability decreased progressively with increasing extract concentration (87.5%, 85.8%, and 84.6% for F1, F2, and F3, respectively). F1 was selected as the optimal base formulation based on its superior foam stability and lowest specific gravity at the minimum effective extract concentration. Betel leaf essential oil was subsequently incorporated into F1 at 0.5%, 1%, and 2%, and antibacterial activity against Escherichia coli was assessed using the disk diffusion method. Inhibition zones of 23.8, 24.2, and 33.0 mm were recorded at 0.5%, 1%, and 2%, respectively, all classified as very strong antibacterial activity. The combination of 20% soapberry extract (F1) with 2% betel leaf essential oil was identified as the most optimal formulation.